COMMUNITY PERCEPTION OF THE EFFECTIVENESS OF USING E-MONEY IN NORTH SUMATRA AS A PAYMENT SYSTEM - Chandra Simanjuntak; Mutiara Sitinjak; Cronika Tambunan; Choms i Gary Sibaran (Universitas Negeri Medan, 2021)
This E-money is a non-cash payment service. Based on data from Bank Indonesia, North Sumatra representative of digital financial services was able to record transactions worth Rp 346 billion at the end of 2018. For 2019 electronic money transactions in North Sumatra are expected to continue to increase. Seeing this phenomenon, through this research we want to find out how the public perception about the effectiveness of using e-money as a payment system in North Sumatra. Researchers used TAM (Technology Acceptence Model) as the basis for conducting research. This research uses a quantitative descriptive research using primary data by collecting data through 450 questionnaires that have been collected and analyzed to examine hypotheses related to the model. The results of the study indicate that the perception of benefits significantly influences the effectiveness of using e-money with a significance value of 0.00 < 0.05. Perceptions of convenience significantly influence the effectiveness of using e-money with significance values 0.00 < 0.05. Trust has a significant effect on the effectiveness of using e-money with significant value 0.00 < 0.05. And all variables X have a simultaneous effect on the effectiveness of e-money (Y) usage by 70.3%.